Case Report: Autologous Bone Marrow Derived Intrathecal Stem Cell Transplant for Autistic Children - A Report of Four Cases and Literature Review - Kobinia, Georg S.; Zaknun, John J.; Pabinger, Christof; Laky, Brenda (Frontiers in Pediatrics, 2021)
Despite steadily growing numbers of children diagnosed with autism spectrum disorders (ASD), causative treatment is unavailable. Recently, biological cell therapies involving pluripotent cells have raised hopes towards sustained beneficial outcome. We herein report data of four children diagnosed with ASD, who were treated with autologous, bone marrow (BM)-derived, intrathecally and simultaneously intravenously applied, point-of-care stem cell transplant (SCT). The three boys and one girl received the diagnosis at ages between 2-4 years. The decision to perform the procedure was preceded by limited beneficiary impact of conventional symptom-based, psychological and pharmacological interventions. At ages of 4-14 years the children received their SCT, no immediate or late adverse events were reported. Disappearance of symptoms were observed by the parents during the following year and consequently improved Autism Treatment Evaluation Checklist (ATEC) scores were reported. The SCT procedure, in trained hands, can be a safe and promising treatment option in children with ASD, responding in a non-satisfactory manner to conventional treatments. It is postulated that SCT may, among others, assert its positive effect by counteracting a cerebral inflammatory autoimmune process which in turn supports the responsiveness to behavioral and pharmacological interventions. Our results in this small group are encouraging, but certainly need further investigation in larger cohorts.